Trend 1976 - 2011. Statistics Canada. CANSIM: Income, Pensions, Spending and Wealth - Personal and Household Taxation | Country: Canada | Province: Newfoundland and Labrador | Table: Income tax, by economic family type and after-tax income quintiles, 2011 constant dollars | Variable: Fourth quintile, Average income tax, All family units | Units: , 1976-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-123. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Income, Pensions, Spending and Wealth - Personal and Household Taxation | Country: Canada | Province: Newfoundland and Labrador | Table: Income tax, by economic family type and after-tax income quintiles, 2011 constant dollars | Variable: Fourth quintile, Average income tax, All family units | Units: , 1976-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-123. Dataset: Presents statistics on taxes paid by Canadian households and individuals, including sales taxes, income tax, property taxes, municipal taxes, provincial taxes, and federal taxes. Calculated statistics such as effective tax rates and marginal tax rates are also covered. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Taxes, Household Income, Households, Tax Liabilities, Taxable Income